The resource curse: a statistical mirage? - James, A (University of Oxford, 2014)
A surprising feature of resource-rich economies is slow growth. It is often argued that natural-resource production impedes development by creating market or institutional failures. This paper establishes an alternative explanationa slow-growing resource sector. A declining resource sector is disproportionately reflected in resource-dependent countries. Additionally, there is little evidence that resource dependence impedes growth in non-resource sectors. More generally, this paper illustrates the importance of considering industry composition in cross-country growth regressions.